THE EFFECTIVENESS OF GENTA EDUCATIONAL GAMES IN OPTIMIZING THE POTENTIAL OF CHILDREN WITH SPECIAL NEEDS: A STUDY ON TEACHERS AT SDN JULANG - Sukmanasa, Elly; Mulyawati, Yuli; Maeysa, Aries (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to enhance the competencies of SDN Julang teachers in optimizing the potential of students with special needs (ABK) through the Game and Educational Tool for Talent Development (GENTA). Using a participatory action research approach, 52 participants (teachers and parents) were trained via workshops and mentoring. Pre- and post-test results showed a 40.7% improvement in understanding ABK concepts, a 56.6% increase in digital media use, and a 63.6% enhancement in implementing GENTA. Qualitative data indicated that 90% of teachers found GENTA effective in increasing ABK students’ motivation. Additionally, students exhibited significant progress in focus and social engagement. This program demonstrates the efficacy of integrating educational games to foster inclusive education and highlights the need for ongoing training to ensure sustainability.